Clitic Climbing, the Raising-Control Dichotomy and Diaphasic Variation in Croatian - Zrinka Kolaković; Edyta Jurkiewicz-Rohrbacher; Björn Hansen (Rasprave Instituta za Hrvatski Jezik i Jezikoslovlje, 2019)
In the paper, we discuss the phenomenon of clitic climbing (CC) out of infinitive complements in contemporary Croatian. Based on the first theoretical work and some empirical findings on CC in Czech and Bosnian, Croatian and Serbian (BCS) and the observation that differences in CC linked to register have been reported for some languages, we elaborate on the claim that CC varies in respect of both register and the Raising-Control Dichotomy. The following research questions are addressed: Does clitic climbing out of the single infinitive in Croatian depend on the type of complement-taking predicate (CTP) with respect to the Raising-Control Distinction? Does CC appear with equal frequency in standard and colloquial Croatian if the type of CTP verb (Raising vs Control) as a variable remains constant? Our study is based on data for two types of complement-taking predicates: a) Raising (8 different verbs) and b) Subject Control (8 non-reflexive + 8 reflexive verbs). The data was extracted from the Forum subcorpus of hrWaC v2.2 and from the Croatian Language Repository and Croatian National Corpus. Our data suggest that not only the Raising-Control Dichotomy, but also diaphasic variation have an impact on CC from infinitive complements.